Kriminalvården och Barnkonventionen - Staaf, Annika; Björkhagen Turesson, Annelie (Socialvetenskaplig tidskrift, 2023)
The Swedish Prison and Probation Service’s and the UN Convention on the Rights of the Child Children belonging to incarcerated parents are typically a marginalised group within society who are often devoid of efficient support. This article discusses the realisation of children’s rights within the Swedish Prison and Probation Services based on the perspectives of staff members. This qualitative study has employed data collection through thematic interviews with staff at five institutions. In this article, the following four themes have been discussed: the difference in children’s rights based on a parent’s gender, the rights of a child to contact their incarcerated parent, the participation of a child within the Swedish Prison and Probation Services, and the staff’s thoughts on the Prison Service’s child rights perspective, current and future. The results display traditional norms continue to steer work within the Swedish Prison and Probation Services, partly creating differences in how children’s rights are realised, resulting in largely unseen parenting from fathers. There exist good examples of such realisations; however, a child’s perspective is largely influenced by staff commitment and individual interests. In implementing the CRC, respondents suggested an accompaniment of children placed in central units with their parents to provide the necessary support from educated staff. Furthermore, there is an additional desire for improved cooperation with social services.